2015
DOI: 10.1128/aem.03167-14
|View full text |Cite
|
Sign up to set email alerts
|

Propionyl Coenzyme A (Propionyl-CoA) Carboxylase in Haloferax mediterranei: Indispensability for Propionyl-CoA Assimilation and Impacts on Global Metabolism

Abstract: Haloarchaea represent a distinct group of Archaea that typically inhabit hypersaline environments, in which nutrient supplies could vary considerably over time. Therefore, most of these extremophiles have developed the adaptation mechanism of depositing poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) intracellularly to store carbon and energy when carbon sources are oversupplied and utilizing PHBV in the absence of exogenous carbon sources (1, 2). During the process of PHBV biosynthesis and utilization, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
(72 reference statements)
1
25
0
Order By: Relevance
“…Furthermore, the genome analysis of the sequenced haloarchaea species implied that PHA-accumulating haloarchaeal strains may mobilize the storage compound during carbon starvation through the β-oxidation cycle as mediated by PhaJ1 ( Figs 7 and 2A ). The final products of acetyl-CoA and propionyl-CoA could be assimilated efficiently via methylaspartate cycle or glyoxylate cycle 35 36 and the propionyl-CoA carboxylation pathway 37 in many haloarchaea. Integration of the PHA mobilization to either general β-oxidation cycle or the following specific pathways may reflect the evolutionary adaptation of haloarchaea to a high-salt environment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the genome analysis of the sequenced haloarchaea species implied that PHA-accumulating haloarchaeal strains may mobilize the storage compound during carbon starvation through the β-oxidation cycle as mediated by PhaJ1 ( Figs 7 and 2A ). The final products of acetyl-CoA and propionyl-CoA could be assimilated efficiently via methylaspartate cycle or glyoxylate cycle 35 36 and the propionyl-CoA carboxylation pathway 37 in many haloarchaea. Integration of the PHA mobilization to either general β-oxidation cycle or the following specific pathways may reflect the evolutionary adaptation of haloarchaea to a high-salt environment.…”
Section: Discussionmentioning
confidence: 99%
“…Cell growth measurement and residual glucose determination. The growth of H. mediterranei strains was monitored by the diphenylamine colorimetric method as described previously (36). The DNA content of cells was quantified by the absorbance at 595 nm using a Beckman Coulter DU800 spectrophotometer (Jersey City, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics make H. mediterranei a potential industrial strain for PHA production. In previous years, our research group has reported PHBV synthesis and its regulation in H. mediterranei (28,(34)(35)(36). In addition, an improved PHBV-producing variant, ES1 with a deletion of genes for exopolysaccharide (EPS) production, was constructed (37).…”
mentioning
confidence: 99%
“…Currently, halophilic microbes are found to be a promising group as PHA-accumulating organisms [15]. They live in halophilic conditions and possess many advantages over non-halophilic microbes [15][16][17][18][19]. Most halophilic archaea can synthesize PHBV from structurally unrelated carbon sources such as starch, glucose, and glycerol [20][21][22].…”
Section: Introductionmentioning
confidence: 99%